Development Administration: Challenges and Strategies for Sustainable Governance in the 21st Century - Syafaruddin Syafaruddin (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Development administration represents a critical intersection between public administration theory and practical development implementation. This research examines the evolution of development administration, analyzing its theoretical foundations, contemporary challenges, and emerging strategies for effective governance in developing nations. Through a comprehensive review of literature and case studies, this study identifies key factors that contribute to successful development administration, including institutional capacity building, participatory governance, technological integration, and sustainable resource management. The findings suggest that effective development administration requires a multifaceted approach that balances top-down policy implementation with bottom-up community engagement, while leveraging modern technologies and maintaining long-term sustainability perspectives.